The effectiveness of group CBT module in alleviating body dissatisfaction, anxiety, and self-esteem issues in adolescents - Nordiana Terence,; Norzihan Ayub,; Patricia Kimong, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines the efficacy of a Cognitive Behavioural Group Counselling Intervention Module in addressing body image dissatisfaction, anxiety, and self-esteem, specifically among adolescents which can have a substantial impact on their mental well-being. Excessive preoccupation with achieving a desired weight and physical appearance can result in the development of depression, eating disorders, and social difficulties. 20 psychology education students took part in this study. They utilised various instruments including the multidimensional body self-relations questionnaire-appearance scale, physical appearance state and trait anxiety scale, and body esteem scale for adolescents and adults. Results of module 0.897 show that the Cognitive Behavioral Group Counselling Intervention Module has high validity and reliability indicating that this intervention module has the potential to assist individuals in altering their assumptions and beliefs related to dissatisfaction with their self-image, specifically to their physical appearance. Additionally, the results of the three variables also show a significant difference between pre and post treatment with p<0.05.